Social preference is maintained in mice with impaired startle reflex and glutamate/D-serine imbalance induced by chronic cerebral toxoplasmosis - Mariana Acquarone (Nature Portfolio, 2021)
Abstract Toxoplasma gondii is an opportunistic protozoan pathogen with a wide geographic distribution. The chronic phase of toxoplasmosis is often asymptomatic in humans and is characterized by tissue cysts throughout the central nervous system and muscle cells. T. gondii and other pathogens with tropism for the central nervous system are considered risk factors in the etiology of several neuropsychiatric disorders, such as schizophrenia and bipolar disorder, besides neurological diseases. Currently, it is known that cerebral toxoplasmosis increases dopamine levels in the brain and it is related to behavioral changes in animals and humans. Here we evaluate whether chronic T. gondii infection, using the cystogenic ME-49 strain, could induce behavioral alterations associated with neuropsychiatric disorders and glutamatergic neurotransmission dysfunction. We observed that the startle amplitude is reduced in the infected animals as well as glutamate and D-serine levels in prefrontal cortical and hippocampal tissue homogenates. Moreover, we did not detect alterations in social preference and spontaneous alternation despite severe motor impairment. Thus, we conclude that behavioral and cognitive aspects are maintained even though severe neural damage is observed by chronic infection of C57Bl/6 mice with the ME-49 strain.